2021
DOI: 10.31557/apjcp.2021.22.6.1883
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retrovirus-H Long Terminal Repeat- Associating Protein 2 (HHLA2) is a Novel Immune Checkpoint Protein in Lung Cancer which Predicts Survival

Abstract: Background: Lung cancer is one of the most frequently diagnosed malignancies. Human endogenous retrovirus-H long terminal repeat-associating protein 2 (HHLA2) is a recently discovered ligand of the B7 family. Blocking this immune checkpoint has become an important treatment option for lung cancer. Methods: The study includes 62 biopsy specimens either bronchoscopic or CT-guided biopsies diagnosed as lung cancer in Hospitals of Faculty of Medicine, Mansoura University, Egypt during the period from 2016 to 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…While both proteins are part of oncogenic signaling pathways, HHLA2 has been detected in several human cancers [ 195 ]. HHLA2 was found to be overexpressed in basal breast cancer [ 357 ], triple-negative breast cancer [ 357 ], colorectal cancer [ 358 ], lung cancer [ 359 , 360 , 361 ], liver cancer [ 362 ], bladder urothelial carcinoma [ 363 ], ccRCC [ 364 , 365 , 366 ], pancreatic cancer [ 367 , 368 , 369 ], osteosarcoma [ 370 ], oral squamous cell carcinoma [ 371 ], and many other cancers [ 357 , 364 ] compared to adjacent normal tissue or healthy controls. Additionally, elevated HHLA2 protein levels were associated with tumor size, tumor stage, lymph node metastasis, and low relapse-free and overall survival in these cancers [ 357 , 358 , 359 , 360 , 361 , 362 , 363 , 364 , 365 , 366 , 367 , 368 , 369 , 370 , 371 ].…”
Section: Discussion Of Novel Options For Cancer Treatment Facilitated...mentioning
confidence: 99%
See 1 more Smart Citation
“…While both proteins are part of oncogenic signaling pathways, HHLA2 has been detected in several human cancers [ 195 ]. HHLA2 was found to be overexpressed in basal breast cancer [ 357 ], triple-negative breast cancer [ 357 ], colorectal cancer [ 358 ], lung cancer [ 359 , 360 , 361 ], liver cancer [ 362 ], bladder urothelial carcinoma [ 363 ], ccRCC [ 364 , 365 , 366 ], pancreatic cancer [ 367 , 368 , 369 ], osteosarcoma [ 370 ], oral squamous cell carcinoma [ 371 ], and many other cancers [ 357 , 364 ] compared to adjacent normal tissue or healthy controls. Additionally, elevated HHLA2 protein levels were associated with tumor size, tumor stage, lymph node metastasis, and low relapse-free and overall survival in these cancers [ 357 , 358 , 359 , 360 , 361 , 362 , 363 , 364 , 365 , 366 , 367 , 368 , 369 , 370 , 371 ].…”
Section: Discussion Of Novel Options For Cancer Treatment Facilitated...mentioning
confidence: 99%
“…HHLA2 was found to be overexpressed in basal breast cancer [ 357 ], triple-negative breast cancer [ 357 ], colorectal cancer [ 358 ], lung cancer [ 359 , 360 , 361 ], liver cancer [ 362 ], bladder urothelial carcinoma [ 363 ], ccRCC [ 364 , 365 , 366 ], pancreatic cancer [ 367 , 368 , 369 ], osteosarcoma [ 370 ], oral squamous cell carcinoma [ 371 ], and many other cancers [ 357 , 364 ] compared to adjacent normal tissue or healthy controls. Additionally, elevated HHLA2 protein levels were associated with tumor size, tumor stage, lymph node metastasis, and low relapse-free and overall survival in these cancers [ 357 , 358 , 359 , 360 , 361 , 362 , 363 , 364 , 365 , 366 , 367 , 368 , 369 , 370 , 371 ]. Thus, HHLA2 might not only become a suitable prognostic marker, as shown by Zhang et al (2021) in a Chinese cohort [ 372 ], but also a potential immunotherapy target for patients who do not respond to other immune checkpoint inhibitors, such as PD-1 inhibitors.…”
Section: Discussion Of Novel Options For Cancer Treatment Facilitated...mentioning
confidence: 99%
“…EGFR Epidermal growth factor receptor (EGFR) is a growth factor receptor involved in cell differentiation and proliferation [35] . B7 family members are affected by EGFR tyrosine kinase inhibitor resistance in gastric cancer [30] , and HHLA2 expression is higher in the EGFR mutant group in lung cancer [36] , [37] , [38] . There is a negative correlation between EGFR and HHLA2 expression in cell lines and non-small-cell lung carcinoma [39] .…”
Section: Hhla2 Kir3dl3 and Tmigd2 In The Immune Microenvironmentmentioning
confidence: 99%
“…Overexpressed in multiple human cancer types, the prognostic role of HHLA2 remains controversial ( Table 1 ). Several studies indicated that overexpression of HHLA2 in tumour cells was associated with unfavorable clinical outcomes and shorter survival rate in patients with prostate cancer, 26 neuroendocrine tumours, 27 hepatocellular carcinoma, 28 , 29 , 30 lung adenocarcinoma, 31 , 32 , 33 , 34 gastric cancer, 35 oral squamous cell carcinoma, 36 bladder urothelial carcinoma, 37 intrahepatic cholangiocarcinoma, 38 colorectal carcinoma, 39 , 40 osteosarcoma, 41 and triple negative breast cancer. 17 On the contrary, HHLA2 was a protective factor predicting low mortality rate in patients with pancreatic cancer, 14 , 42 , 43 epithelial ovarian cancer, 44 malignant glioma, 45 and recurrent or unresectable advanced gastric cancer.…”
Section: Role Of Hhla2 In Cancer Developmentmentioning
confidence: 99%